Hydrodynamic effects of large-scale suspended mussel farms: Field observations and numerical simulations - Zhong, Wei; Lin, Jun; Zou, Qingping; Wen, Ying; Yang, Wei; Yang, Guanlin (Frontiers in Marine Science, 2022)
The hydrodynamic effects of the largest suspended mussel farms in the East China Sea near Gouqi Island, was investigated using a high-resolution 3D ocean model and field observations. To capture the farm effects on hydrodynamics, an additional momentum sink term was introduced in the model. The model results compared well with the observations. The present model and observational results indicate that the presence of farms reduces the flow by more than 79%, 55%, and 34% in the upper, middle, and bottom layers at the farm center, respectively. According to the harmonic analysis of predicted current, mussel farms reduce the magnitude of semidiurnal tidal current and also alter the magnitude and direction of the diurnal tidal current. The blockage by the farm weakens the Eulerian residual tidal current within the farm in NE-SW direction, while strengthens that at the edge of the farm in SE-NW direction. Cross sections, Sec1 and Sec2 are perpendicular to these two major residual current and intercept with the center of the farm from SE to NW and from NE to SW respectively. The farm effect on the total water flux over a month through the Sec2 displays a semi-lunar periodic oscillation and it is one order smaller than that at Sec1. An asymmetry tidal current was observed in the farm north of Gouqi Island. The field observation of vertical profiles of current suggest that the thickness of surface canopy boundary layer can reach 5m upstream the farm during flood tide, increases gradually down-stream, and up to 10m under the cumulative influences of the farm. And a wake zone was observed downstream of the farm during flood tide. Understanding farm-induced hydrodynamic effects provides insight into how to optimize farm layouts based on local hydrodynamics, to maximize farm productivity and minimize the environmental impacts.